2021
DOI: 10.1093/jacamr/dlab164
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in patients with suspected urinary tract infections in primary care in Assam, India

Abstract: Objectives We investigated the prevalence and diversity of antimicrobial resistance in bacteria isolated from urine samples of community-onset urinary tract infection (UTI) patients in southern Assam, India. Methods Freshly voided midstream urine samples were collected from patients attending primary healthcare centres, with the patients’ epidemiological data also recorded. Species identification was confirmed using a VITEK 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Paul et al . [ 27 ] previously reported a 26.2% ESBL prevalence in Assam (NE India), whereas Behera et al . [ 28 ] reported 43% combined prevalence in E. coli and Klebsiella pneumoniae from community UTIs from E. India, and, in 2021, Kumar et al [ 29 ] reported a 46.6% ESBL prevalence in E. coli from Uttarakhand in N India.…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al . [ 27 ] previously reported a 26.2% ESBL prevalence in Assam (NE India), whereas Behera et al . [ 28 ] reported 43% combined prevalence in E. coli and Klebsiella pneumoniae from community UTIs from E. India, and, in 2021, Kumar et al [ 29 ] reported a 46.6% ESBL prevalence in E. coli from Uttarakhand in N India.…”
Section: Discussionmentioning
confidence: 99%
“…The high susceptibility and more effective in-vitro potential of Isepamicin against gram-negative bacterial isolates, as compared with other aminoglycosides, could be attributed to the lower impact of 1 6'-N-acetyltransferase enzyme on Isepamicin 14 . This enzyme is the most common aminoglycoside-modifying enzyme present in these pathogens and causes resistance to aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies from different geographical locations in India have reported UPEC with a very high rate of drug resistance. 48 , 49 Irrational use of antimicrobial agents in developing countries is considered a major factor responsible for the emergence of MDR strains. 50 The management of UPEC infections is complicated by the occurrence of diverse UPEC with multiple virulence characteristics and resistance to multiple drugs, and by poor socioeconomic conditions in developing countries including India.…”
Section: Discussionmentioning
confidence: 99%